Enhancing Precision Agriculture for Climate Change Mitigation in Visegrad Countries: Factors Shaping Adaptation - Bojana Petrovic; László Csambalik (Land)
As climate change intensifies, organic agriculture faces new challenges in maintaining sustainability and environmental health. Precision agriculture offers climate-smart solutions by enabling resource efficient and data-driven farming. However, the adoption of precision agriculture technologies (PATs) is influenced by various socio-economic factors, behavioral factors, financial factors, institutional factors and technological factors. Adaptation factors for precision agriculture technologies and their application in response to climate change were identified through a systematic literature review (SLR) of 58 papers from journals indexed in Scopus and Web of Science. The investigation was performed for the Visegrad group countries: Czechia, Slovakia, Poland, and Hungary. Some of these technologies include satellite imaging, remote sensing, soil moisture sensors, and precision irrigation systems, which enable more efficient use of water, fertilizers, and energy. Through a comparative analysis of the application of precision agriculture technologies in the V4 countries, this review underscores the importance of tailored PA approaches to address a specific climate challenge and promote sustainable agricultural practices in the V4 countries.